Feasibility study for grid-connected biomass and biogas - Marsadek M.; Kumaran V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biogas; Biomass; Critical fault clearing time; Feasibility studies; Feed-in tariff; Grid-connected; Power system studies; Electric power transmission networks